A Rapid Monoclonal Antibody-Based Enzyme Immunoassay (EIA) for the Quantitative Determination of Soluble Fibrin in Plasma - Nieuwenhuizen, W; Hoegee-De Nobel, E; Laterveer, R (Thrombosis and Haemostasis, 1992)
Soluble fibrin is considered as a molecular marker for intravascular fibrin formation, and impending thrombotic events. Most of the existing assays are less suitable for routine clinical applications and their specificity may be limited.We have developed a sandwich-type EIA with a fibrin-specific MoAb described by us before (Proc Natl Acad Sci 1989; 86: 8951) as the capture antibody. An other MoAb (G8; Thromb Haemostas 1988; 60: 415) with an epitope in the carboxyl-terminal sections of the fibrin α-chains, was labeled with peroxidase and used as the tagging antibody. The EIA is calibrated against plasma spiked with known concentrations of soluble fibrin. The time-to-result of the EIA is only 1.5 h. Concentrations as low as 0.5 µg soluble fibrin/ml plasma are readily measurable. Heparin has no effect on the results. Fibrinogen and fibrin(ogen) degradation products are not detected. The values of fibrinopeptide A and soluble fibrin values found with the “COA-SET soluble fibrin” assay correlated well with the soluble fibrin values found with our EIA i.e. r = 0.998 and 0.984, respectively. The run-to-run variabilities were 7.9% and 6.6% for samples with low and high soluble fibrin concentrations, respectively. The within-run variabilities were 2.5, 1.8, 4.0 and 4.6% for samples with 1, 0.5, 0.25 and 0.125 µg soluble fibrin/ml, respectively.The sensitivity, specificity, accuracy and short time-to-result make our EIA suitable for routine clinical applications and the monitoring of the effectivity of heparinization.